Improving Descriptive Text Writing Skills Using Magic Card Media in English Subjects in Class X of Parmonangan High School - Sinaga, Aldo LM (Lembaga Riset Mutiara Akbar, 2023)
The aim of this research is to determine the extent to which class X students' skills have improved in writing descriptive text. The research was conducted in Class This research was also used to determine the extent to which students' knowledge and learning attitudes increased during learning. The method used in this research is the Classroom Action Research method with a cycle technique consisting of two action cycles, namely cycle I and cycle II. The data collection tools used for quantitative data were daily written tests and qualitative data used observation or observation sheets, self-reflection sheets, peer assessment sheets, and performance assessment rubrics. The research results show that magic card media can improve descriptive text writing skills. Learning Completeness increased from the initial condition of 28.13% to 50% in cycle I and increased to 84.38% in cycle II. The increase in students' skills in writing descriptive text reached 5.31% of the average learning outcomes in the pre-cycle, and learning outcomes in cycle II increased by 6.40% from the average learning outcomes in cycle I.